Blockchain as the basis of the digital economy. World experience of cryptocurrency financial regulation - Shmatko, Alexander; Gavrilova, Alla (My University, 2019)
The article discusses the international experience of cryptocurrency regulation on the example of such countries as the United Kingdom, the United States of America, Canada, Australia, Estonia, Ukraine, Japan, China, Latin American countries. If we consider the world map, which shows the status of cryptocurrency, then we can mark the countries that have been waiting. These countries include Venezuela, the USA, Canada, Australia, a part of the European Union, and such giants of technological innovations as China and Japan. A number of countries of the European Union, led by Germany, Latin American countries are in a neutral position, due to the lack of developed legislation aimed at regulating cryptocurrency relations. Cryptocurrencies in Ecuador, India, Nepal, Thailand, Vietnam and Bangladesh banned. The conclusion about the expediency of legal regulation of new phenomena, including internationally.
Keywords: bitcoin; cryptocurrency; blockchain; fintech; IT; debt market; ethereum